2023
DOI: 10.1007/s10584-023-03484-6
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ social networks and regional spillover effects in agricultural climate change mitigation

Abstract: Climate change poses a severe threat to global agricultural production and rural livelihoods, and since agriculture itself is a significant source of greenhouse gas (GHG) emissions, it can also play an important role in climate change mitigation. This article investigates how farmers’ social networks influence the adoption of on-farm mitigation strategies. More precisely, we use a network autocorrelation model to explore the relationship between a farmer’s own mitigation behavior and the mitigation behavior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Seeking conformity and a feeling of belonging has even been found to have stronger implications for behavioural change than financial incentives (Kuhfuss et al, 2013). Moreover, particularly in our case study region, farmers were found to learn from and imitate (perceived) knowledgeable peers (Kreft, Angst et al, 2023) and trust relationships can help to lower the perceived risks of adoption (Sligo & Massey, 2007).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 85%
See 4 more Smart Citations
“…Seeking conformity and a feeling of belonging has even been found to have stronger implications for behavioural change than financial incentives (Kuhfuss et al, 2013). Moreover, particularly in our case study region, farmers were found to learn from and imitate (perceived) knowledgeable peers (Kreft, Angst et al, 2023) and trust relationships can help to lower the perceived risks of adoption (Sligo & Massey, 2007).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 85%
“…These are exogenous parameters based on a farm survey (Kreft et al, 2020). (3) A social network between farmers representing personal exchange of knowledge on climate change mitigation derived from a social network analysis based on face‐to‐face interviews (Kreft, Angst et al, 2023; Kreft, Angst, et al, 2021). Most individual and social factors could be taken into account without further transformation.…”
Section: Methods: Agent‐based Modelling Framework Farmindmentioning
confidence: 99%
See 3 more Smart Citations